2008
DOI: 10.1074/jbc.m800127200
|View full text |Cite
|
Sign up to set email alerts
|

Thrombin-activable Fibrinolysis Inhibitor Zymogen Does Not Play a Significant Role in the Attenuation of Fibrinolysis

Abstract: Activated thrombin-activable fibrinolysis inhibitor (TAFIa) plays a significant role in the prolongation of fibrinolysis. During fibrinolysis, plasminogen is activated to plasmin, which lyses a clot by cleaving fibrin after selected arginine and lysine residues. TAFIa attenuates fibrinolysis by removing the exposed C-terminal lysine residues. It was recently reported that TAFI zymogen possesses sufficient carboxypeptidase activity to attenuate fibrinolysis through a mechanism similar to TAFIa. Here, we show wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
24
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 31 publications
1
24
0
Order By: Relevance
“…Only a relatively small percentage (<1%) of available TAFI is activated in plasma when clotting is initiated with low levels of thrombin [31]. As recently reported, the percentage of FVIII in plasma greatly influences TAFI activation over the interval between clot formation and tPA induced clot lysis [14] especially in the range of 0–10% FVIII.…”
Section: Discussionmentioning
confidence: 99%
“…Only a relatively small percentage (<1%) of available TAFI is activated in plasma when clotting is initiated with low levels of thrombin [31]. As recently reported, the percentage of FVIII in plasma greatly influences TAFI activation over the interval between clot formation and tPA induced clot lysis [14] especially in the range of 0–10% FVIII.…”
Section: Discussionmentioning
confidence: 99%
“…Because protein MCP inhibitors eliminate the activity of both TAFI and TAFIa, it is difficult to design experiments that distinguish between the activities of the two forms. Consequently, studies with MCP inhibitors against TAFIa activity to argue that TAFI activity is irrelevant will have to be reconsidered (69,70).…”
Section: Discussionmentioning
confidence: 99%
“…Foley et al . demonstrated that TAFI is effective in cleaving a small substrate, but due to its inability to cleave plasmin‐modified fibrin, the authors concluded that it had no effect on the attenuation of fibrinolysis. In addition to the intrinsic zymogen activity, Mishra et al .…”
Section: Introductionmentioning
confidence: 99%
“…However, Willemse et al [13] suggested that the clot lysis experiments reported by Valnickova were compromised by in vitro activation of TAFI. Foley et al [14] demonstrated that TAFI is effective in cleaving a small substrate, but due to its inability to cleave plasmin-modified fibrin, the authors concluded that it had no effect on the attenuation of fibrinolysis. In addition to the intrinsic zymogen activity, Mishra et al [15] demonstrated that it is possible to enhance the zymogen activity of TAFI by nanobodies.…”
Section: Introductionmentioning
confidence: 99%